Predicting Temporal Gait Kinematics: Anthropometric Characteristics and Global Running Pattern Matter - Patoz A. Aurelien; Lussiana T. Thibault; Gindre C. Cyrille; Mourot L. Laurent (2021, 2021)
Title screen